Hedonistic Lifestyle, Self-Control, and E-Wallet Use in Relation to Student Financial Management in Malang - Meidilla R Hatyani; Rheni Anggraini (IJBAMS: International Journal of Business Accounting Management Social Science, 2026)
College students' financial behavior has been influenced by advances in digital financial technology, particularly regarding personal financial management. Maintaining financial stability for college students has become challenging due to the ease of access to e-wallet transactions, variations in self-control, and lifestyle preferences. The purpose of this study was to examine how self-control, e-wallet use, and a hedonistic lifestyle influence college students' financial management in Malang City. This study combined an explanatory strategy with a quantitative approach. Purposive sampling was used to collect primary data from 160 college students in Malang City who use e-wallets. Multiple linear regression was used to analyze the data. The results showed that self-control and e-wallet use had a significant impact on college students' financial management, while a hedonistic lifestyle had no effect. These results suggest that self-control and wise e-wallet use have a greater impact on college students' financial management compared to hedonistic lifestyle choices.